Combining Electrospinning and Electrode Printing for the Fabrication of Stretchable Organic Electrochemical Transistors - Lerond, Michael; Subramanian, Arunprabaharan; Skene, W. G.; Cicoira, Fabio (Frontiers in Physics, 2021)
Stretchable conductors and organic electrochemical transistors (OECT) were fabricated from PEDOT:Tos (poly(3,4-ethylenedioxythiophene):iron tosylate) nanofibers. The devices were prepared by a combination of electrospinning and electrode printing followed by vapor phase polymerization (VPP). The impact of both the processing time and the composition of three electrospinning mixtures on the electrospun fiber mats was evaluated by scanning electron microscopy and cyclic voltammetry. Fibrillar mats prepared from the different mixtures maintain their electrical properties were stretched to 140% of their original length. Stretchable OECTs were fabricated by printing silver drain and source electrodes directly on the conductive spun fibers. The fabricated devices showed a field effect behavior under a 50% strain.